Azimuthal correlations in Z plus jets events in proton-proton collisions at ?s=13TeV - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Damanakis, K.; Dragicevic, M. (Springer, 2023)
The production of Z bosons associated with jets is measured in pp collisions at v s = 13 TeV with data recorded with the CMS experiment at the LHC corresponding to an integrated luminosity of 36.3 fb(-1). The multiplicity of jets with transverse momentum pT > 30 GeV is measured for different regions of the Z boson's pT(Z), from lower than 10 GeV to higher than 100 GeV. The azimuthal correlation Delta phi between the Z boson and the leading jet, as well as the correlations between the two leading jets are measured in three regions of p(T)(Z). The measurements are compared with several predictions at leading and next-to-leading orders, interfaced with parton showers. Predictions based on transverse-momentum dependent parton distributions and corresponding parton showers give a good description of the measurement in the regions wheremultiple parton interactions and higher jet multiplicities are not important. The effects of multiple parton interactions are shown to be important to correctly describe the measured spectra in the low pT(Z) regions.